ACCOUNTING IN BUDGETARY ORGANIZATIONS AND ITS COMPLIANCE WITH INTERNATIONAL STANDARDS - Nilufar Umarova (European Science Publishing, 2025)
Accounting in budgetary organizations plays a crucial role in ensuring the efficient allocation and management of public funds. In many countries, including Uzbekistan, the transition to international accounting standards has been a significant aspect of financial reforms aimed at improving transparency, accountability, and financial governance. This study explores the principles of accounting in budgetary organizations, focusing on their compliance with international standards such as International Public Sector Accounting Standards (IPSAS). The adoption of IPSAS enhances financial reporting, ensures comparability, and strengthens fiscal discipline in budgetary institutions. However, the implementation process presents challenges, including legal adjustments, capacity building, and technological advancements. This research highlights the current state of accounting in budgetary organizations, analyzes the level of compliance with international standards, and discusses the implications for economic governance in Uzbekistan. By examining existing policies, regulations, and best practices, the study provides recommendations for improving the effectiveness and reliability of accounting in public sector entities.
Keywords: Accounting, Budgetary Organizations, International Standards, IPSAS, Financial Reporting, Fiscal Discipline, Economic Governance, Public Sector Accounting.